2007
DOI: 10.1029/2006jf000487
|View full text |Cite
|
Sign up to set email alerts
|

Intertidal sand body migration along a megatidal coast, Kachemak Bay, Alaska

Abstract: [1] Using a digital video-based Argus Beach Monitoring System (ABMS) on the north shore of Kachemak Bay in south central Alaska, we document the timing and magnitude of alongshore migration of intertidal sand bed forms over a cobble substrate during a 22-month observation period. Two separate sediment packages (sand bodies) of 1-2 m amplitude and $200 m wavelength, consisting of well-sorted sand, were observed to travel along shore at annually averaged rates of 278 m/yr (0.76 m/d) and 250 m/yr (0.68 m/d), resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… Rubin [2004] and Buscombe and Masselink [2009] have developed similar systems for examining sand bed grain size parameters at scales of a few centimeters. This technology has been extended for application on gravel‐sized particles [ Adams et al , 2007; Ruggiero et al , 2007].…”
Section: Introductionmentioning
confidence: 99%
“… Rubin [2004] and Buscombe and Masselink [2009] have developed similar systems for examining sand bed grain size parameters at scales of a few centimeters. This technology has been extended for application on gravel‐sized particles [ Adams et al , 2007; Ruggiero et al , 2007].…”
Section: Introductionmentioning
confidence: 99%
“…The migration speeds of bars in the megatidal setting of Regnéville inlet accelerated before welding onto the high-tide beach, whereas the migration speeds of bars monitored by FitzGerald [1984,1988] in a microtidal to weakly mesotidal setting decelerated as bars approached the high-tide beach due to lesser exposure to waves. Working on intertidal sand bodies (not inlet vicinity swash bars) in a megatidal embayment in Alaska, Adams et al [2007] also identified pulses in migration speeds that they related to wave energy variations. The acceleration of bar migration speeds in Normandy is probably due to larger wave energy at high tide as the bar approaches the high-tide beach.…”
Section: Robin Et Al: Bar Migration and Shoreline Changesmentioning
confidence: 99%
“…In recent geologic history, the 1964 Valdez earthquake redirected the mouth of the river nearly 2.5 km south of its previous position, coinciding with 1–2 m of subsidence in the area (Coulter & Migliaccio, 1966). In Homer, directly across Kachemak Bay from the WRD (~5 km), the mean maximum semidiurnal tidal range is 5.6 m, with extreme tides exceeding 9 m. Mean wave heights are 0.5 and 0.8 m for summer and winter, respectively, although they have been observed in excess of 2.5 m (Adams et al, 2007). These oceanographic conditions enable a powerful means to recirculate seawater back through the porous media of the WRD and effectively pump nutrients and solutes via SGD pathways.…”
Section: Study Areamentioning
confidence: 99%